Nurses’ Viewpoints on Implementation of Continuing Education Programs at Hospitals - Malekshahi, Farideh; Rezaian, Jafar; Fallahi, Shirzad; Almasian, Mohammad (Journal of Medicine, 2019)
Background: Continuing education programs (CEP) are among the most common methods of bringing the medical staff, especially the nurses, up-to-date. Evaluation of the implementation of CEP is needed to optimize such programs and to eliminate any faults. This study aimed to identify the viewpoints of the nurses about CEP in 2015. Materials & methods: The study was carried out on all the 750 nurses working in the hospitals of the Lorestan province using the census method. From among these 750 nurses, 537 were included in the study. The data collection instrument was a researcher-designed self-administered questionnaire including demographic information and some questions regarding the necessity of CEP, obstacles to the implementation and the methods of implementation of such programs. Results: The findings showed that 42.6% of the participants considered it very important that CEP be implemented. 48.8% of the participants considered the presentation of educational materials on compact disks (CDs) as the most appropriate method. 53.1% considered a time interval of once a month in the mornings for the implementation of the CEP as appropriate. Conclusions: According to results, continuing education plays an important role in nursing, and the continuation of such educational programs as well as improving their quality is highly necessary J MEDICINE JUL 2019; 20 (2) : 80-86